2010
DOI: 10.1103/physreve.82.031404
|View full text |Cite
|
Sign up to set email alerts
|

Time-resolved viscoelastic properties during structural arrest and aging of a colloidal glass

Abstract: Evolution of the energy landscape during physical aging of glassy materials can be understood from the frequency and strain dependence of the shear modulus but the nonstationary nature of these systems frustrates investigation of their instantaneous underlying properties. Using a series of time-dependent measurements we systematically reconstruct the frequency and strain dependence as a function of age for a repulsive colloidal glass undergoing structural arrest. In this manner, we are able to unambiguously ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
38
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 27 publications
6
38
0
Order By: Relevance
“…Cocard et al (2000) observed a similar ageing behaviour for Laponite gels that displayed a rapid increase in gel modulus initially and then a slow increase after that, but the plateau state was not attained in the experiment. Other studies by Willenbacher (1996) and Negi and Osuji (2010) reported similar results. At complete structural rejuvenation, the yield value was 65 Pa at 0.005 M KNO 3 and 90 Pa at 0.01 M KNO 3 .…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Cocard et al (2000) observed a similar ageing behaviour for Laponite gels that displayed a rapid increase in gel modulus initially and then a slow increase after that, but the plateau state was not attained in the experiment. Other studies by Willenbacher (1996) and Negi and Osuji (2010) reported similar results. At complete structural rejuvenation, the yield value was 65 Pa at 0.005 M KNO 3 and 90 Pa at 0.01 M KNO 3 .…”
Section: Resultssupporting
confidence: 86%
“…For instance, "Wigner glass" or repulsive glass is formed as a result of long-range Coulombic interactions where the interparticle distance to be much larger than the particle diameter. Such phase is obtained for extremely low volume fractions and low ionic strength (Bonn et al, 1998;Negi and Osuji, 2010). The elasticity of gel is determined by the infinite percolated network while that of glass is determined from caging effects (Tanaka et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Associated with this shear-banding effect, which is asymmetric between the up and downsweep, is a hysteresis effect in the local velocimetry measurements, as characterised by A v in Eq. (11). As can be seen in Fig.…”
Section: Fluidity Modelmentioning
confidence: 65%
“…These two types of behavior allow to us to distinguish between colloidal gels that experience an irreversible yielding transition [16][17][18][19], and colloidal gels that can be rejuvenated due to the shear-reversible nature of the interparticle attractive interactions such as van der Waals or depletion interactions [20][21][22][23]. The re- * Corresponding author: ajhart@mit.edu covery step of the latter category of gels has been termed "rheological aging" and the kinetics of such phenomena are a complex function of the volume fraction, the nature of the interparticle interactions and the shear history [24][25][26][27][28][29]. Being able to tailor the yielding, flow and recovery of colloidal gels is crucial to achieving the desired shape, mechanical integrity and microstructure in direct-write 3D printing and molding.…”
Section: Introductionmentioning
confidence: 99%